Periodontal disease and intra-amniotic complications in women with preterm prelabor rupture of membranes. (2nd November 2018) - Radochova, Vladimira; Kacerovska Musilova, Ivana; Stepan, Martin; Vescicik, Peter; Slezak, Radovan; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective: Periodontal disease is frequently suggested as a possible causal factor for preterm delivery. The link between periodontal disease and preterm delivery is a possible translocation of periopathogenic bacteria to the placenta and amniotic fluid as well as a systemic response to this chronic inflammatory disease. However, there is a lack of information on whether there is an association between clinical periodontal status in women with preterm prelabor rupture of membranes (PPROM) and the presence of microbial invasion of the amniotic cavity (MIAC) and intra-amniotic inflammation (IAI). Therefore, the main aim of this study was to evaluate the incidence and severity of periodontal disease in women with PPROM. The secondary aim was to characterize an association between periodontal status and the presence of intra-amniotic PPROM complications (MIAC and/or IAI). Materials and methods: Seventy-eight women with PPROM at gestational ages between 24 + 0 and 36 + 6 weeks were included in this study. The samples of amniotic fluid were obtained at admission via transabdominal amniocentesis, and amniotic fluid interleukin (IL)-6 concentrations were determined using a point-of-care test. All women had a full-mouth recording to determine the periodontal and oral hygiene status. Probing pocket depth and clinical attachment loss were measured at four sites on each fully erupted tooth. Results: In total, 45% (35/78) of women with PPROM had periodontal disease. Mild, moderate, and severe periodontal disease was present in 19% (15/78), 19% (15/78), and 6% (5/78) of women, respectively. The presence of MIAC and IAI was found in 28% (22/78) and 26% (20/78) of women, respectively. Periopathogenic bacteria (2 × Streptococcus intermedius and 1 × Fusobacterium nucleatum ) was found in the amniotic fluid of 4% (3/78) of women. There were no differences in periodontal status between women with MIAC and/or IAI and women without these intra-amniotic complications. Conclusions: The presence of MIAC and IAI was not related to the periodontal status of women with PPROM.